A Clinician's Guide to Pemphigus Vulgaris - Khan Mohammad Beigi, Pooya (Springer International Publishing, 2018)
This book, summarizing much of what is known about pemphigus vulgaris, features topics including categories of the disorder, clinical symptoms, diagnosis and treatment, and six recent clinical research studies about the disease. Giving dermatologists, dermatology residents, and primary care physicians a deeper insight into pemphigus vulgaris, a rare autoimmune disease characterized by blisters and rosision on the skin and mucous membranes, A Clinician's Guide to Pemphigus Vulgaris provides insight and treatment options alongside dozens of high quality photographs, illustrations, and clinical tables detailing the disease at all stages. The text also provides over 20 clinical case photos of patients exhibiting symptoms.